The Impact of ICT in empowering Sarawak women in home-based business communities - Norizuandi Ibrahim,; Azlina Bujang,; Zainon Hj Bibi,; Sarehan Sadikin,; Noriham Bujang,; Siti Hafizah Ambi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In alignment with the sustainability strategy focusing on good governance, sustainable development, and racial harmony, this study investigates the access, use, and effects of ICT training on women in Sarawak. Its primary objective is to assess how ICT training benefits women in managing small home-based businesses. Data was gathered through questionnaires from 62 participants who attended training sessions in various Sarawak locations: Kota Samarahan, Sri Aman, Sarikei, Kuching, and Bako. This research holds significant importance for the state government, as it strives to increase the number of individuals with ICT skills and narrow the digital divide between urban and rural areas. The study reveals a strong consensus among respondents regarding the positive impact of ICT on empowering women, boosting their self-esteem, enriching their knowledge and skills, benefiting the socio-economic community, and fostering efficient management practices. The findings offer valuable insights into the effectiveness of ICT training for Sarawakian women engaged in home-based businesses. The mean scores for all variables indicate high agreement among respondents, with values exceeding four for each variable. This study underscores the substantial role of ICT in knowledge dissemination and empowering individuals, particularly in advancing gender equality. It suggests that ICT is an invaluable tool for successful training in rural areas and underscores the need for a systematic strategy to enhance ICT literacy.